The relationship between deep breathing relaxation techniques and reducing anxiety and patient quality of life heart failure undergoing treatment at Sidikalang Regional Public Hospital - Hutagalung, Perak Maruli Asi Roha (Universitas Aisyah Pringsewu, 2024)
Cardiovascular disease (CVDs) is the main cause of death globally, dying around 17.9 million people every year WHO (World Health Organization. In Asia and the Pacific Islands, deaths that occur due to cardiovascular disease and congenital cardiovascular disease reach 33% of all deaths A study conducted by Framingham stated that heart failure in men (per 1000 incidents) increased from 3 at the age of 50 - 59 years to 27 at the age of 80 - 89 years, and heart failure in women was measured to be one third lower than in men. 2018 Riskedas data revealed 3 provinces with the highest prevalence of heart disease, namely North Kalimantan province 2.2%, DIY and Gorontalo 2%, followed by Southeast Sulawesi 1.9%, North Sulawesi 1.8% then Aceh 1.6%. West Sumatra 1.6%, DKI Jakarta 1.6%, West Java 1.6%, East Java 1.6% and Central Java 1.6%. Stress is one of the triggers for hypertension, both in the elderly, young adults and middle age. The body's reactions due to stress include shortness of breath, heart palpitations and cold sweat. Untreated anxiety can lead to irrational behavior, conflict, disobedience, fear, inability to carry out daily activities and feelings of fear of death. Deep breathing exercises have many benefits, namely that they are easy to do independently, require no money and are practical. An initial survey conducted at the Sidikalang Regional General Hospital of patients who experienced heart failure and were undergoing treatment, there were 3 patients who said that the patients experienced stress and anxiety about their illness. Research purposes : to determine the level of anxiety before and after, quality of life before and after and to determine the relationship between breathing relaxation techniques in reducing anxiety and the quality of life of heart failure patients at Sidikalang Hospital. The sample in the study was 60 people. Output: Scientific article accredited by Sinta 2. The TKT of this research is TKT 3. Results: 1) Characteristics of respondents: the majority of respondents are 55-74 years old, 39 people (65%), the majority have a high school education, 45 people (75%), the majority work as farmers, 42 people (70%), the majority are male, 35 people (58.34). %). 2) The majority of patients' anxiety levels before being given breathing relaxation techniques were moderate, 28 people (46.67%). 3) The majority of patients' anxiety level after being given the breath relaxation technique was moderate 47 people (78.33%), 4) The majority of patients' quality of life before being given the breath relaxation technique was poor 49 people (81.66%), 5) The quality of life of the patient after being given the technique 45 people (75%) had poor breathing relaxation. The Asymp.Sig value is 0.000 less than 0.05, meaning that there is a significant relationship between reducing anxiety and quality of life after being given the deep breathing relaxation technique to heart failure patients undergoing treatment at the Sidikalang Regional General Hospital.